(untitled) (Medical Forum Monthly, 2024)
Objective: To examine the indications outcomes of choledochoduodenostomy (CDD) in patients presented with common bile duct stone. Study Design: Retrospective/Observational study. Place and Duration of Study: This study was conducted at the Department of Surgery, Central Park Medical College and Allied Hospitals Lahore from July 2017 to June 2018. Materials and Methods: Thirty patients of both genders presented with refusal or failed ERCP and common bile duct stone size was >1cm were included in this study. Patients detailed demographic including age, sex and indications of CDD were recorded after written consent. All the patients received CDD. Complications associated with procedure were examined. Mortality rate was also examined. Patients were followed for 1 year after surgical treatment. Data was analyzed by SPSS 24.0. Results: Twenty (66.67%) patients were females and 10 (33.33%) patients were males. 12 (40%) patients were ages 35 to 50 years, 13 (43.33%) patients were ages 51 to 65 years and 5 (16.67%) had ages above 65 years. Failed ERCP was the commonest indication found in 12 (40%) patients followed by refusal of ERCP and recurrent stones. Respiratory complications found in 4 (13.33%) patients, wound infections in 10% patients, anastomotic leak in 1 patient and 1 (3.33%) patient had cholangitis. None of patient had recurrence of CBD and none of patient found to have sump syndrome. Mortality found in 1 (3.33%) patients Conclusion: Choledochoduedenostomy is safe and effective treatment modality with fewer rates of complications.